2012
DOI: 10.1128/jb.00903-12
|View full text |Cite
|
Sign up to set email alerts
|

The Periplasmic Nitrate Reductase Nap Is Required for Anaerobic Growth and Involved in Redox Control of Magnetite Biomineralization in Magnetospirillum gryphiswaldense

Abstract: ABSTRACTThe magnetosomes of many magnetotactic bacteria consist of membrane-enveloped magnetite crystals, whose synthesis is favored by a low redox potential. However, the cellular redox processes governing the biomineralization of the mixed-valence iron oxide have remained unknown. Here, we show that in the alphaproteobacteriumMagnetospirillum gryphiswaldense Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
120
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 66 publications
6
120
0
Order By: Relevance
“…It is interesting to note that these latter elements are known to be cofactors of metalloenzymes (32) that are essential for bacterial growth and metabolism. Molybdenum is indeed required for nitrate reductase enzymatic activity, which has been reported in AMB-1 and other MTB strains (33,34). The nitrate reductase reduces nitrate for cell respiration and is also necessary for the magnetite biomineralization in strains MSR-1 and AMB-1 (33, 34).…”
Section: Resultsmentioning
confidence: 97%
“…It is interesting to note that these latter elements are known to be cofactors of metalloenzymes (32) that are essential for bacterial growth and metabolism. Molybdenum is indeed required for nitrate reductase enzymatic activity, which has been reported in AMB-1 and other MTB strains (33,34). The nitrate reductase reduces nitrate for cell respiration and is also necessary for the magnetite biomineralization in strains MSR-1 and AMB-1 (33, 34).…”
Section: Resultsmentioning
confidence: 97%
“…1a,b). In the absence of oxygen, cells developed distinct tactic bands at millimolar concentrations in gradients of nitrate (an alternative terminal electron acceptor for anaerobic respiration 14 , Supplementary Fig. 1a), indicating that the strong aerotaxis behaviour is part of a general energy taxis response similar to that identified in the microaerophilic A. brasiliense and other bacteria [15][16][17][18] .…”
Section: Resultsmentioning
confidence: 98%
“…Recently, it has been shown that dissimilatory denitrification is essential to form proper magnetosomes under microaerobic conditions (51). A nitrate reductase nap mutant formed small and poorly crystallized magnetite reminiscent of that of the ftsZm mutant but, in contrast to the latter, also in the presence of nitrate.…”
Section: Discussionmentioning
confidence: 99%